The prevalence and effect of burnout on graduate healthcare students (Canadian Medical Education Journal, 2017)
Burnout is a growing epidemic among professional healthcare students. Unaddressed burnout has been shown to have psychological and performance related detriments. The purpose of this scoping literature review was to investigate the prevalence of burnout and its effects on the psychological, professional, empathetic ability, and academic acuity of graduate healthcare students. Inclusion criteria included English language papers published within the last 10 years and subjects in graduate healthcare professional programs. This search encompassed 8,214 articles. After title and abstract screening, 127 articles remained and were sorted into five domains of interest: etiology, professionalism, mental health, empathy, and academic performance. After duplicates were removed, 27 articles remained for the scoping review. Graduate level healthcare students had higher levels of burnout than age matched peers and the general population. The high prevalence of burnout within graduate healthcare students can have an effect on their mental health, empathy, and professional conduct. Understanding the occurrence and effects of burnout within graduate healthcare programs allows faculty and administration to plan curriculum, and provide information to students to understand, recognize, and create opportunities to decrease burnout in order to create long lasting quality clinicians.